Linear and nonlinear light beam propagation in chiral nematic liquid crystal waveguides - Laudyn, Urszula Anna; Kwaśny, Michał; Jung, Paweł; Trippenbach, Marek; Assanto, Gaetano; Karpierz, Mirosław (Photonics Letters of Poland, 2016)
We employ a thick layer of chiral nematic liquid crystals to demonstrate the evolution of a one-dimensional (1D) higher-order guided mode into a beam self-confined in both transverse dimensions at various wavelengths. We also report the experimental observation of higher-order modes guided by soliton-induced waveguides in chiral nematic liquid crystals. Full Text: PDF References M. Peccianti, A. Dyadyusha, M. Kaczmarek, G. Assanto, "Tunable refraction and reflection of self-confined light beams", Nature Phys. 2, 737 (2006). CrossRef G. Assanto, M.A. Karpierz, "Nematicons: self-localised beams in nematic liquid crystals", Liq. Cryst. 36, 1161 (2009). CrossRef M. Peccianti, G. Assanto, "Nematicons", Phys. Rep. 516, 147 (2012). CrossRef A. Piccardi, G. Assanto, L. Lucchetti, F. Simoni, "All-optical steering of soliton waveguides in dye-doped liquid crystals", Appl. Phys. Lett. 93 (17), 171104 (2008). CrossRef A. Pasquazi, A. Alberucci, M. Peccianti, G. Assanto, "Signal processing by opto-optical interactions between self-localized and free propagating beams in liquid crystals", Appl. Phys. Lett. 87 (26), 261104 (2005). CrossRef M.-F. Shih, M. Segev, G. Salamo, "Circular waveguides induced by two-dimensional bright steady-state photorefractive spatial screening solitons", Opt. Lett. 21, 931 (1996). CrossRef M. Peccianti, G. Assanto, A. De Luca, C. Umeton, I. C. Khoo, "Electrically assisted self-confinement and waveguiding in planar nematic liquid crystal cells", Appl. Phys. Lett. 77, 7 (2000). CrossRef J. Petter, C. Denz, "Guiding and dividing waves with photorefractive solitons", Opt. Commun. 188, 55 (2001). CrossRef M. Peccianti, G. Assanto, "Signal readdressing by steering of spatial solitons in bulk nematic liquid crystals", Opt. Lett. 26 (21), 1690 (2001) CrossRef Y.V. Isdebskaya, A.S. Desyatnikov, G. Assanto, Y. Kivshar, "Multimode nematicon waveguides", Opt. Lett. 36, 184 (2011). CrossRef P. Oswald, P. Pieranski, Nematic and Cholesteric Liquid Crystals (Taylor & Francis 2005). CrossRef A. Laudyn, M. Kwasny, M.A. Karpierz, "Nematicons in chiral nematic liquid crystals", Appl. Phys. Lett. 94, 091110 (2009). CrossRef U.A. Laudyn, P. Jung, K.B. Zegadło, M.A. Karpierz, G. Assanto, "Power-induced evolution and increased dimensionality of nonlinear modes in reorientational soft matter", Opt. Lett. 39 (22), 6399 (2014). CrossRef F. Sala, M.A. Karpierz, "Modeling of molecular reorientation and beam propagation in chiral and non-chiral nematic liquid crystals", Opt. Expr. 20(13), 13923 (2012). CrossRef U. Laudyn, P. Jung, M.A. Karpierz, G. Assanto, "Quasi two-dimensional astigmatic solitons in soft chiral metastructures", Sci. Rep. 6, 22923 (2016). CrossRef